Accepted Manuscripts (Quarterly Journal of Economics, 1986)
Journal Article Accepted Manuscripts Get access The Quarterly Journal of Economics, Volume 101, Issue 3, August 1986, Pages 659–661, https://doi.org/10.1093/qje/101.3.659 Published: 01 August 1986